101 Systematic review of controlled trials in the treatment of mitochondrial disorders. Issue 3 (9th February 2012) - Pfeffer, G; Thorburn, D; Turnbull, D; Majamaa, K; Chinnery, P F
Abstract : Background: Mitochondrial respiratory chain disorders are the most prevalent group of inherited neurometabolic diseases. Treatment is supportive, although some treatments report disease-modifying efficacy in isolated cases and small trials. This review evaluates the efficacy of these treatments. Objectives: To identify any objective evidence to support the use of current treatments for mitochondrial disease. Methods: We searched various clinical trials registers and medical literature databases up to the end of 2009, for clinical trials in mitochondrial disease. Studies with a high risk of bias were excluded. Interventions included any pharmacological agent, dietary modification, nutritional supplement, exercise therapy or other treatment. Results: 1335 abstracts were reviewed, and from this 19 abstracts were identified for further review. Upon detailed review, ten studies fulfilled the entry criteria. Three trials used creatine monohydrate. One trial studied the effects of a combination of coenzyme Q10, creatine monohydrate, and lipoic acid. Some of these demonstrated improvement in surrogate markers but no clinical benefit. Five trials studied the effects of dichloroacetate: three trials in children (improvement in biochemical markers only) and two trials in adults (long-term study terminated early due to peripheral nerve toxicity). One trial using dimethylglycine showed no significant effect. Excluded trials are also discussed. Conclusions: There is currently no clear evidence supporting the use of any intervention in mitochondrial disorders. Further research is needed to establish the role of a wide range of therapeutic approaches.